2001
DOI: 10.1007/s10024001-0085-3
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Plexus Carcinomas and Rhabdoid Tumors: Phenotypic and Genotypic Overlap

Abstract: Five of six poorly differentiated choroid plexus carcinomas identified at our institution contained cells displaying a rhabdoid phenotype. Immunoperoxidase stains showed focal positivity for cytokeratin, epithelial membrane antigen, glial fibrillary acidic protein, S100, and vimentin. The MIB-1 proliferative index ranged from 7.0% to 27.1%. All six tumors were p53 positive. Only the one child with Li-Fraumeni syndrome had a p53 germline mutation. Electron microscopy verified choroid plexus differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 10 publications
1
16
1
Order By: Relevance
“…The presence of necrosis has been considered as malignancy criteria (20,21). None of the cases in our series had notable necrosis, either on the MRI or under a microscope, which is consistent with the benign nature of CPPs.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of necrosis has been considered as malignancy criteria (20,21). None of the cases in our series had notable necrosis, either on the MRI or under a microscope, which is consistent with the benign nature of CPPs.…”
Section: Discussionsupporting
confidence: 76%
“…Cases were classified according to the WHO nomenclature 26 as papilloma (PP) and carcinoma (CA). We further divided the carcinomas into well [WCA] or poorly differentiated [PCA], similarly to what was done by others 21,27 . Five cases of normal fetal choroid plexus (NFCP) (between 16 and 40 gestational weeks) were also studied to compare their immunohistochemical pattern with those of tumors.…”
Section: Methodsmentioning
confidence: 99%
“…22,24 However, glioblastoma cases have been described where the sarcomatous components show osteo-chondrogenic or rhabdoid differentiation. [25][26][27] In such cases, cytogenetic analysis demonstrated that both the glioblastoma and mesenchymal component share identical abnormalities, suggesting a common clonal origin. 25 In addition, recent studies have shown that a subclass of glioblastoma exhibits molecular and phenotypic mesenchymal features, raising the question about the cellular origin of these tumors.…”
Section: Discussionmentioning
confidence: 99%